2020
DOI: 10.1136/neurintsurg-2019-014735
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of contact aspiration and the stent retriever technique versus stent retriever alone for recanalization in acute cerebral infarction: the randomized ASTER 2 study protocol

Abstract: RationaleMechanical thrombectomy (MT) using a stent retriever (SR) device is currently the recommended treatment in ischemic stroke due to anterior circulation large vessel occlusion. Combining contact aspiration (CA) with SR is a promising new treatment, although it was not found to be superior to SR alone as first-line treatment for achieving successful reperfusion.AimTo determine whether endovascular treatment combining first-line use of CA and SR is more efficient than SR alone.MethodsThe ASTER 2 clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 34 publications
1
27
0
1
Order By: Relevance
“…Furthermore, it is reported that endovascular treatment combined with intravenous pharmacological thrombolysis may provide increased efficacy to many patients with ischemic stroke (Lowhagen Henden et al, 2017). Endovascular mechanical thrombectomy has also shown great benefits in large vessel occlusion via a combination of contact aspiration and stent retrievers (Mokin et al, 2014;Lapergue et al, 2020). However, despite the potential benefits, endovascular mechanical thrombectomy treatment is limited by high costs, its need for trained personnel, and its inability to restore tissue function within the penumbra.…”
Section: Di-3-n-butylphthalide (Nbp)mentioning
confidence: 99%
“…Furthermore, it is reported that endovascular treatment combined with intravenous pharmacological thrombolysis may provide increased efficacy to many patients with ischemic stroke (Lowhagen Henden et al, 2017). Endovascular mechanical thrombectomy has also shown great benefits in large vessel occlusion via a combination of contact aspiration and stent retrievers (Mokin et al, 2014;Lapergue et al, 2020). However, despite the potential benefits, endovascular mechanical thrombectomy treatment is limited by high costs, its need for trained personnel, and its inability to restore tissue function within the penumbra.…”
Section: Di-3-n-butylphthalide (Nbp)mentioning
confidence: 99%
“…Klisch and colleagues, reports an increased median total recanalization time of 60 minutes (interquartile range 45 to 87 minutes) compared with standard mechanical thrombectomy using single-stent retrieval (range 20 to 48 minutes). Complete recanalization (TICI 2b/3) was achieved in 8 out of 10 cases, with good clinical outcomes (m Rankin Scale score of 2 or less) in 5 patients [2,7,8].…”
Section: Dual Stent Retrievermentioning
confidence: 93%
“…If necessary the microcatheter can be retracted further to clear the tip of the aspiration catheter optimizing the integration with the thrombus. At the end, the stent retrieval is retracted while continuous negative suction is applied through a pump or manually with an aspiration syringe ( Figure 6) [8,10]. The PROSPECT Technique (proximal balloon occlusion together with direct thrombus aspiration during stent retriever thrombectomy) is combining the use of BGC with large bore distal aspiration catheters that are navigated to the face of the thrombus before retrieving the clot with a stent retriever device.…”
Section: Combined Treatmentmentioning
confidence: 99%
“…retrieval force, thus optimizing the MT results. 54 If pre-procedural CTA evaluation reveals extreme tortuosity in the supra-aortic vessels that will be an obstacle for catheterization of supra-aortic vessels and guide catheter positioning, we favor the use of a base catheter such as the Neuron™ MAX, Benchmark™, or Chaperon™ (Microvention, Aliso Viejo, CA, USA), together with local aspiration either alone or in combination with SR. If the initial CTA assessment shows that navigation of a BGC is feasible, we use it with an IC to overcome tortuosity of cervical arteries and proceed with local aspiration alone or combined technique (Table 2).…”
Section: Techniques For Challenging Cervical Arteriesmentioning
confidence: 99%
“…The use of IC for MT allows easy negotiation of tortuosity in cerebral vessels or distal cervical segments of the vertebral and carotid arteries, providing adequate stability for microcatheter vessel selection into intracranial vasculature. ICs also straighten the cervical and intracranial access, which facilitates SR removal by ensuring a more favorable vector for retrieval force, thus optimizing the MT results [ 54 ].…”
Section: Unfavorable Vascular Anatomy In Cervical Arteriesmentioning
confidence: 99%